Right atrial spleen. Issue 3 (September 1985) - Kuijer, P; Dion, R; van Merrienboer, F
Abstract : A large cardiac tumour occupying most of the right atrium and the right ventricle and causing inflow obstruction to the right heart was confirmed by cross sectional echocardiography in a 41 year old man. After surgical resection histological examination showed that the atrial tumour had the characteristics of splenic tissue. Possible mechanisms for the development of such a tumour include an origin analogous to that of an accessory spleen or the implantation and subsequent growth of lymphoid tissue in a pre-existing superior vena caval or high right atrial angioma.